Importance of Lactate Dehydrogenase, Cortisol, Dopamine, Zinc, and Vitamin D3 in Iraqi Patients with Polycystic Ovary Syndrome - Mohammed, Noor A.; Sulaiman, Ghassan M.; Alabassi, Hazima M. (Iraqi Journal of Science, 2025)
Polycystic ovary syndrome (PCOS) comprises a multiplex hormone-based disorder that is typically accompanied by several complications, including irregularity of menses, excessiveness of hair growth in face and body, acne, obesity, diminished fertility, and higher probability of developing diabetes. Many hormones and enzymes may undergo changes in PCOS patients. This study involved 138 women who were separated into two groups: PCOS women (n=90) with an age range of (22-45) years, and apparently healthy women (n=48) representing the control group with age being matched to the patient group. All patients attended to Al-Kadhimiya Teaching Hospital, Department of Obstetrical and Gynecology and diagnosed by a consultant physician. Following peripheral blood withdrawal (5 ml) from participants, serum was isolated and placed in an Eppendorf tube until used. ELISA kit was used to determine serum levels of some biochemical parameters (Lactate dehydrogenase, cortisol, dopamine, zinc, and vitamin D3). The results showed that LDH level was significantly elevated (P<0.0001) in PCOS patients (2.55±0.70) compared with the control (1.16±0.18). While, significantly lower levels of cortisol, dopamine, zinc and vit D3 (P<0.0001) were demonstrated in PCOS group (4.30±1.62, 48.45±26.27, 5.21±1.85 and 271.19±36.07, respectively), compared with the control (9.40±0.76, 252.52±47.47, 8.26±1.42, and 328.82±21.33, respectively). The study found an elevation in the serum level of LDH in PCOS patients compared to control, while cortisol, dopamine, zinc, and Vit D3 recorded a significant decrease in patients as compare to control.